2022
DOI: 10.3390/cancers14030667
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Epigenomic and Genomic View on Phyllodes and Phyllodes-like Breast Tumors

Abstract: Fibroepithelial lesions (FL) of the breast, in particular, phyllodes tumors (PT) and fibroadenomas, pose a significant diagnostic challenge. There are no generally accepted criteria that distinguish benign, borderline, malignant PT and fibroadenomas. Combined genome-wide DNA methylation and copy number variant (CNV) profiling is an emerging strategy to classify tumors. We compiled a series of patient-derived archival biopsy specimens reflecting the FL spectrum and histological mimickers including clinical foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…A recent study revealed that borderline phyllodes tumor could be separated into either benign or malignant PTs using molecular assays (27). Interestingly, in our study, the hierarchical clustering heatmap show several borderline phyllodes cases clustered with the malignant PTs group, and some clustered closely with the benign phyllodes tumor group (supplement Fig.…”
Section: Discussionsupporting
confidence: 60%
“…A recent study revealed that borderline phyllodes tumor could be separated into either benign or malignant PTs using molecular assays (27). Interestingly, in our study, the hierarchical clustering heatmap show several borderline phyllodes cases clustered with the malignant PTs group, and some clustered closely with the benign phyllodes tumor group (supplement Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Conversely, a mildly cellular PT that has well‐circumscribed margins, few mitoses, barely discernible atypia, and no stromal overgrowth, but a very focally infiltrative border, may on occasion render a degree of diagnostic hesitation. A recent study on methylation and copy number analysis of FELs found that the methylation profiles of PT and FA converge in a distinct cluster, while the copy number profiles of these FELs suggest that they may be separated into benign [flat copy number profiles/few copy number variants (CNVs)] and malignant (high CNVs) categories, the implication being that borderline PTs may separate into benign and malignant forms based on such analysis, thus potentially obviating the need for a discrete “borderline” grade 53 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study on methylation and copy number analysis of FELs found that the methylation profiles of PT and FA converge in a distinct cluster, while the copy number profiles of these FELs suggest that they may be separated into benign [flat copy number profiles/few copy number variants (CNVs)] and malignant (high CNVs) categories, the implication being that borderline PTs may separate into benign and malignant forms based on such analysis, thus potentially obviating the need for a discrete "borderline" grade. 53 Johannes M€ uller, in 1838, conferred the appellation "cystosarcoma phyllodes" 54 (from the Greek: kystis [pouch, bladder], sarkoma [fleshy tumour] and phyllon [leaf]), accompanied by a "complete and comprehensive" description. 55 The term that now stands, "phyllodes tumour (Tumore Filloide)," was devised by Lomonaco in 1960.…”
Section: R E C U R R E N T C H a L L E N G E Smentioning
confidence: 99%
“…Top differentially methylated probes were determined by calculating standard deviations across the entire dataset comprising >18,000 cases obtained from public resources including TCGA and the Gene Expression Omnibus (GEO), as well as from in‐house reference collections ( n = 18 537, case Sentrix IDs and coordinates in Appendix S1). Filtered set of methylation beta values were compared by uniform manifold approximation projection (UMAP) for dimension reduction, as previously described 18,19 . Copy number plots were generated with conumee (in R, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…Filtered set of methylation beta values were compared by uniform manifold approximation projection (UMAP) for dimension reduction, as previously described. 18,19 Copy number plots were generated with conumee (in R, Vienna, Austria). All methylation data and annotations were curated in our public methylation analysis platform EpiDiP (www.epidip.org).…”
Section: O P Y N U M B E R V a R I A T I O N A N D M E T H Y L A T I ...mentioning
confidence: 99%